Cambodia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper discusses major economic developments in Cambodia in 1997. It discusses developments in the real sector and factors accounting for output growth, estimated at 2 percent in 1997, down from 6 1\2 percent in 1996. The paper analyzes developments affecting inflation during the year, examines public finance, and highlights the persistent problems with revenue collection that, together with overspending on the military budget, led to a squeeze in civilian nonwage expenditure. The paper also analyzes monetary and financial sector developments.